DIGITAL COMIC MEDIA FOR MATHEMATICAL LITERACY DEVELOPMENT IN EDUCATION: A CONTEXTUAL APPROACH - Nenden Suciyati Sartika; Peni Permatasari; Ika Meika (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2025)
The purpose of this research is to produce a valid and practical contextual digital comic media for eighth-grade circle material. The research and development were conducted using the ADDIE R&D model. The research began with the stages of analysis, design, development, implementation, and evaluation. The developed digital comic was validated by expert validators: material experts, language experts, and media experts. The material experts scored 95.2%, with very valid criteria, the language experts scored 84%, with very valid criteria, and the media experts scored 84.6%, with very valid criteria. The validation results of the digital comic, validated by the expert validators, indicated that the digital comic was suitable for limited testing with students to determine its practicality. The digital comic, which had previously been revised based on the suggestions and input from the expert validators, was presented. The limited trial began with a small group trial with an average percentage of 85.5%, categorized as very practical, followed by a large group trial with an average percentage of 85.6%, categorized as very practical. The limited trial was conducted in class VIII D of SMPN 2 Menes. Posttest results showed that digital comics were able to support students' mathematical literacy skills, with high average scores in the small group trial of 18 and the large group of 18, with a stable standard deviation of 1.25 for the small group and 1.76 for the large group. Thus, digital comics, in addition to being practical, can also support students' mathematical literacy skills.